The power of Youtube in popular culture dissemination: the case of Bakar Production - Iswahyudi Tejo Yuwono (Institute of Computer Science (IOCS), 2023)
The advancement of communication and information technology is a necessity. One of them is new media technology in the video and audio platform called Youtube. Youtube is a social media that is at the peak of its glory in today's masses. Popular culture is born from YouTube so quickly regardless of the class of society. This research aims to describe how Balekambang kethoprak artists maintain their economic status and continue to work in a space that no longer exists. New media in the YouTube platform is the vehicle for disseminating their work. The research is an empirical qualitative research, with the subjects being the artists who are members of the Balekambang kethoprak artists' forum. The data collection technique is observation and direct interviews with subjects on the spot. The guide for extracting data is management theory, as they implement it to maintain their personal lives and artistic lives. The results of the research found that the new media Youtube is an effective tool in disseminating works of art. Especially during the Covid 19 pandemic, new media helped maintain the sustainability of the artists' work, including Balekambang kethoprak artists.